2013
DOI: 10.1161/circimaging.113.000640
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Prediction by Quantitative Right Ventricular Function Assessment in 575 Subjects Evaluated for Pulmonary Hypertension

Abstract: Background-Although right ventricular (RV) dysfunction is a major determinant of outcome in patients with pulmonary hypertension (PH), the optimal measure of RV function is poorly defined. We hypothesized that RV strain measured by speckle-tracking echocardiography predicts outcome in PH over a broad range of pulmonary pressures. Methods and Results-Prospective peak RV longitudinal systolic strain measurement was performed on 575 patients (mean age, 56±18 years; 63% women) referred for echocardiography for kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
289
4
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(343 citation statements)
references
References 47 publications
12
289
4
14
Order By: Relevance
“…They showed that RVFAC better reflects RV systolic function than TAPSE when the pericardium is kept open. Practically, however, there may be more variability in the measure of RVFAC and recent outcome studies carried out by FINE et al [21] suggest that RV longitudinal strain, which was not measured in the current study, is a stronger correlate of survival than RVFAC in prevalent cases of PH.…”
Section: Discussioncontrasting
confidence: 64%
“…They showed that RVFAC better reflects RV systolic function than TAPSE when the pericardium is kept open. Practically, however, there may be more variability in the measure of RVFAC and recent outcome studies carried out by FINE et al [21] suggest that RV longitudinal strain, which was not measured in the current study, is a stronger correlate of survival than RVFAC in prevalent cases of PH.…”
Section: Discussioncontrasting
confidence: 64%
“…An increase in PAPs does not necessarily reflect disease progression and a decrease in PAPs does not necessarily signal improvement. A comprehensive echocardiographic assessment includes a description of chamber sizes, particularly of the RA and RV area, the magnitude of tricuspid regurgitation, the LV eccentricity index and RV contractility, which can be determined by several variables, including RV longitudinal systolic strain/strain rate and RV fractional area change, Tei index and tricuspid annular plane systolic excursion (TAPSE) [101][102][103][104][105][106][107][108].…”
Section: The World Health Organization Functional Class (Who-fc) (Webmentioning
confidence: 99%
“…47,48 Importantly, RV function as estimated by echocardiography and pulmonary hemodynamics as measured by RHC (MPAP, CO, PVR) may independently characterize survival in PAH. 46,49 Our data suggest that the IPVD patients had better RV function (lower median RIMP) than non-IPVD patients at the time of diagnosis of POPH, despite similar hemodynamics. However, survival was worse in the setting of IPVD.…”
Section: Discussionmentioning
confidence: 68%
“…Finally, RIMP is one transthoracic echocardiography measure of RV function; others are evolving. 46 The RIMP calculation is composed of RV isovolumetric contraction time, relaxation time, and ejection time, and the higher the value, the worse the RV function. 47,48 Importantly, RV function as estimated by echocardiography and pulmonary hemodynamics as measured by RHC (MPAP, CO, PVR) may independently characterize survival in PAH.…”
Section: Discussionmentioning
confidence: 99%